APPLICATION OF BENZOTRIAZOLEAS CORROSION INHIBITOR OFAPI 5LX65 IN SODIUM CHLORIDE SOLUTION - P. Yatiman; N. M. Surdia; S. Purwadaria; B. Ariwahjoedi; R. Suratman (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2006)
APPLICATION OF BENZOTRIAZOLEAS CORROSION INHIBITOR OFAPI 5LX65 IN SODIUM CHLORIDE SOLUTION. The inhibition mechanismofAPI 5LX65 carbon steel corrosion by benzotriazole (BTAH) in 0.5% NaCl solution saturated with CO2 at temperatures of 25, 45, 65 and 85 oC was investigated using electrochemical impedance spectroscopy (EIS). The measurements were done on the steel specimens after they were immersed into the test solutions containing BTAH for 30 hours. The polarization resistance, Rp, of each specimen was then determined with respect to electrical equivalent circuit proposed by Randall for a metal which is actively corroding in its environment. The data were then used to calculate the inhibition efficiency and surface coverage of carbon steel by BTAH. It was found that the BTAH concentration and temperatures of the test solutions affected significantly the inhibition efficiency. The presence of carbonic acid decreases the inhibition efficiency, however by using 8.40 mmol/LBTAH the inhibition efficiency had reached more than 90% at all temperatures. The increase of temperature has reduced the surface coverage and has lead to decrease the inhibition efficiency. The re-increase of inhibition efficiency at 85oC was related to the decrease in FeCO3 and CO2 solubility. Moreover, it was revealed that the adsorption of BTAH on the steel surface obeyed the Temkin’s adsorption isotherm.